Asha's response to COVID-19: Providing care to slum communities in India - Jean Oulund Peteet; Louanne Hempton; John R. Peteet; Kiran Martin (Health for All Nations, 2020)
Slum populations, the most vulnerable to COVID-19, are emerging as hotspots for transmission of the virus. Comprehensive strategies for addressing this challenge exist, but reports of effective models for implementing them have been lacking. Asha, a 33-year old health and community development organization in Delhi, India has responded to the pandemic by activating well-developed networks in the community to enact a range of interventions with encouraging results. The success of Asha in controlling COVID-19 in the slums reflects the realization of the values Asha promotes in the community: dignity, empowerment, justice, non-violence, compassion, gratitude, generosity, optimism, joy, and simplicity. Although developed by a team of Christians and those of other faiths on Asha's staff, these values enjoy broad-based support within a pluralistic, Hindu-influenced society.